Determination of the predictive factors of long-lasting insecticide-treated net ownership and utilisation in the Bamenda Health District of Cameroon - Eric B. Fokam; Germaine F. Kindzeka; Leonard Ngimuh; Kevin T. J. Dzi; Samuel Wanji (BMC Public Health, 2017)
Abstract Background Malaria is a serious health concern in Africa. In Cameroon, an endemic country where malaria remains a major public health problem, several control measures have been put in place among which the use of insecticide-treated bednets (LLINs/ITNs) is considered one of the core vector control strategies. However, the greatest challenges include ownership and utilisation by individuals and households. Factors such as age, marital status, gender, education and occupation of the household head, household size, knowledge of bednets, socioeconomic status, and environmental factors have been suggested to have an impact on bednet ownership and utilisation in different settings. The present study sought to determine bednet ownership and utilisation rates and to assess the impact of predictive factors on bednet ownership and use in the Bamenda Health District (BHD) of Cameroon. Methods A cross-sectional study involving 384 households was conducted in six health areas in the BHD. A structured and semi-structured questionnaire was used to collect data on demographic and household characteristics as well as information on their bednet ownership and utilisation. Descriptive statistics, bivariate and multivariate logistic regression analysis were performed. Results Frequency of bednet ownership was relatively high (63.5%) with LLINs being most abundant (91.9%); the majority of households (87.7%) obtained their bednets during the 2011 free distribution campaign. Utilisation was relatively high (69.3%), with negligence (29.3%) and heat discomfort (26.7%) accounting most for non-usage of bednets. Children less than 5 years (63%) and pregnant women (60%) most often used these nets. Households headed by a married couple, those with older household heads, household with smaller size (5–12 persons), and knowledge of bednets (good knowledge) had positive impacts on bednet ownership (p < 0.05). The gender of the household head (males), their educational level, environmental conditions (presence of suitable mosquito breeding sites), bednet number in households (greater number of bednets) and the prioritised groups (children < 5 and pregnant women) had positive impacts on bednet utilisation in households (p < 0.05). There was a negative association between bednet ownership and utilisation by households as bednet ownership was high and utilisation of these nets was low. Marital status and age of household head, household size, and knowledge of bednets had impacts on bednet ownership while gender and educational level of the household head, environmental suitability, the number of bednets and the two prioritised groups had an impact on bednet usage. Conclusion These factors may be relevant for policy makers and in decision making for the intensification of campaign strategies to ensure more effective subsequent distribution campaigns in the BHD and beyond.